1934 S.C. Acts 1288, No. 731, §§ 1-6 - (:unkn) unknown (My University, 1934)
Prohibited transporting, possessing, selling, renting, or giving a firearm or machine gun. Punishable by fine up to $1,000 and imprisonment with solitary confinement up to 20 years.
Keywords: MACHINE GUN RESTRICTION; TRANSFER, MANUFACTURE & POSSESSION